Penerapan Pemasaran Digital Sebagai Upaya Meningkatkan Pendapatan Pada UMKM Saung Tutut Tegalsawah di Kota Karawang - Indra Kusnadi; Netti Nurlenawati; Dini Yani (Journal of Business and Economics Research (JBE), 2022)
Research on UMKM in Tegalsawah Karawang aims to find out how effective the impact is on the application of digital marketing that has been carried out by these UMKM, with processed snails that have been innovated. This research is qualitative research using a descriptive method. In conducting this research, researchers conducted direct observations and interviews with business owners. In these observations, researchers have direct information when observing social media accounts that are run and conducting in-depth interviews with the owner to conduct research. The results of interviews and this research show the positive impact of the application of digital marketing that utilizes social media, which provides an increase in income for UMKM in Saung Tutut Tegalsawah Karawang.